Good boy! - Hanson, Lisa, 1960-; Belson, Kristine; Richardson, Zeke.; Hoffman, John (John Robert); Shannon, Molly, 1964-; Aiken, Liam.; Nealon, Kevin, 1953-; Marin, Cheech; Redgrave, Vanessa, 1937-; Reiner, Carl, 1922-; Burke, Delta; Murphy, Brittany; et al. ([United States] : MGM Home Entertainment, 2004)
Dogs are an alien species sent to earth thousands of years ago to spy on humans. But when the spies stop reporting back to the home planet, Canid 3942 is sent to earth to investigate. Once there, Canid 3942 encounters Owen, a young boy who runs a dog-walking service. Owen befriends the space-dog, renaming him Hubble. When it becomes obvious that the dogs of earth have forgotten their mission, Hubble enlists the help of Owen to get them all into shape before The Great Dane arrives to inspect. If they fail, all of earth's dogs will be recalled to their home planet of Sirius.
Based on "Dogs from outer space" by Zeke Richardson.
English track: Dolby digital 5.1.
French track: Dolby digital 2.0 surround.
Spanish track: Dolby digital 2.0 surround.
Commentary: Dolby digital 2.0.
Special features: dog-umentary with cast and crew interviews; audio canine-tary by director and cast; poochie profiles; "Dog-walking duty" interactive map; "The dog poung" deleted scenes and alternate punchlines; "Crafty canine" featurette; Q&Q with Hubble.
Keywords: Dogs -- Drama; Life on other planets -- Drama; Feature films; Children's films; Films for the hearing impaired